Study on T-Test For Marital Status and Qualification-Wise Analysis of Respondents: Comparative analysis of emotional intelligence based on qualifications and marital status (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Meanvalues for respondents on qualification of analysis of negative emotions (EI1)are 50.383, 50.609 and 48.623 with S.D. value of 6.912, 7.069 and 7.302. Thevalue of F-test is 1.979 at significant level of 0.14. To letting up, it isconcluded that there is no significant difference found (the value ofsignificance level for F-test is greater than 0.05) between the opinion ofrespondents on qualification regarding EI1. The mean values for therespondents on qualification regarding analysis of positive emotions are40.539, 41.232 and 40.026 with S.D. values of 6.934, 5.578 and 5.109. The valueof F-test is 0.775 at 0.462 significance level. It is extracted that there isno significant difference found (the value of significance level for F-test isgreater than 0.05) between the scores of respondents on qualification regardingEI2.